Risk Analysis of Farmers and Rice Milling Businesses: A Study on The Rice Supply Chain in Yogyakarta - Boyke Purnomo; Alifia Maharani Risdianto (Jurnal Manajemen dan Agribisnis, 2025)
Background: Rice is a staple food consumed by more than 98% of households in Indonesia. However, risks along the supply chain create an imbalance between high rice consumption and domestic rice production. Purpose: In response to this circumstance, this study aims to identify the risks in the upstream sector of the rice supply chain involving rice farmers and millers, and then to develop a mitigation strategy for those priority risks. Design/Methodology/Approach: A case study approach was adopted, and primary data were collected through in-depth interviews and questionnaires from farmers and rice millers in five different districts of Yogyakarta Province. Furthermore, the Failure Mode, Effect, and Criticality Analysis (FMECA) method was utilized for risk analysis. Findings/result: The results showed that there are 19 types of risks encountered by farmers, where biological risks (weeds, pests, and diseases) are a priority risk with a moderate criticality level. In addition, the rice millers faced 17 types of risks, with the priority risk being the uncertainty of the raw material supply (rice and grain) with a high criticality level. Conclusion: To manage biological risks, we suggest that farmers utilize applied technology and optimize extension management to improve quality and avoid the risk of decreasing crop yields. For rice millers, we propose the use of diversified supply sources, inventory management, and make-to-order production systems to reduce risk intensity and increase production effectiveness. Originality/value (State of the art):  This study is relevant to current affairs considering that rice production has an impact on national food security and that the risk of the rice supply chain is still inevitable. This study cascades the key risks in the rice supply chain, specifically in Yogyakarta, and assists relevant stakeholders in effectively addressing these risks. Keywords: farmer risk, rice milling, supply chain, risk management, FMECA